Further standardisation in Land Administration - Lemmen, C.H.J. (2020)
The paper describes the ongoing developments and standardisation in land administration. Standards are relevant in relation to build as well as maintain and develop a land administration. Standards like the ISO 19152 Land Administration Domain Model (LADM) are helping to jump-start new initiatives and are connecting top-down and bottom-up projects together. The LADM facilitates the efficient set-up of land administration and can function as the core of any land administration system. LADM is flexible, widely applicable and functions as a central source of state-of-the-art international knowledge on this topic. Some future trends in the domain and the maintenance of the standard are presented and being discussed in the paper. These trends may be relevant for the development of a second edition of the LADM over the coming years.